The Impact of Cost Strategy Policies on Company Performance in the Construction Industry in Brazil - Cavalcanti, Nathalie da Silva; Romano, Cezar Augusto (Revista Gestão da Produção Operações e Sistemas, 2021)
Purpose– This article aims to assess the influence of cost strategy policies on the performance of sole traders, small and medium-sized companies in the civil construction sector in Curitiba and the Metropolitan Region (southern Brazil). Design/methodology/approach– Using a questionnaire, the survey collected data from 95 companies. The data has been analyzed based on descriptive statistics and multivariate analysis using discriminant analysis. Findings– Results showed that a lack of a strategic process is more evident in companies classified as low to medium performance companies. Only 36% of companies are positioned for only one of the positioning strategies. The cost strategy variable, which had the greatest impact on performance, was the policy with “greater simplification/standardization of products/services” compared to the other variables analyzed in the study. Originality/value– Results imply that most companies do not have a strategic position and that it is possible to obtain better performance through strategic management, encouraging the development of this perspective in companies in the sector. Keywords - Construction Industry; Strategy; Strategic management; Cost strategy; Survey.